2015
DOI: 10.18805/ag.v36i4.6671
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of postnatal development of testes and its association with puberty and fertility -A review

Abstract: Indigenous bull breeds attain puberty late in life when compared to the breeds of <italic>Bos taurus</italic>. Cross breeding between <italic>Bos taurus</italic> and <italic>Bos indicus</italic> has decreased the age at puberty and increased the total semen production period of bulls. However, some of the drawbacks like impaired semen production, poor libido, and low freezability are common among the crossbred bulls in India. Leydig and Sertoli cells are the most important n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This is following the research results of Sajjad et al (2007) who reported that GnRH injection in male buffalo did not affect semen volume and pH. Waheed et al ( 2018) stated that administration of GnRH (Theriogon®) did not effect to pH of semen of bull, meanwhile, the volume of semen was higher, Injection of gonadotropin-releasing hormone (GnRH) can increase the multiplication of Sertoli and Ley dig cell, than increasing testicular weight, sperm production, sexual maturity and germ cell count (Kumar et al, 2015;Doroteu et al, 2021). The semen in treatment A showed the best color and consistency of semen compared to treatments B and C (Table 1).…”
Section: Macroscopic Semen Qualitymentioning
confidence: 99%
“…This is following the research results of Sajjad et al (2007) who reported that GnRH injection in male buffalo did not affect semen volume and pH. Waheed et al ( 2018) stated that administration of GnRH (Theriogon®) did not effect to pH of semen of bull, meanwhile, the volume of semen was higher, Injection of gonadotropin-releasing hormone (GnRH) can increase the multiplication of Sertoli and Ley dig cell, than increasing testicular weight, sperm production, sexual maturity and germ cell count (Kumar et al, 2015;Doroteu et al, 2021). The semen in treatment A showed the best color and consistency of semen compared to treatments B and C (Table 1).…”
Section: Macroscopic Semen Qualitymentioning
confidence: 99%
“…Due to the broad substrate specificity of BTH, chain lengths have great importance in glycotechnological applications such as the preparation of varying glycosaminoglycan oligosaccharides (Takagaki et al, 1994). In addition, since it is known that the BTH enzyme is a part of the PH-20 protein, the enzyme is considerably important in penetration and artificial insemination due to its activity (Cherr et al, 2001;Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%